Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1600-6143.2008.02546.x
|View full text |Cite
|
Sign up to set email alerts
|

The Early Course of Kidney Allograft Rejection: Defining the Time When Rejection Begins

Abstract: We studied the early events in mouse kidney allografts and isografts to define when allorecognition begins and when alloimmune tissue injury begins. Allografts but not isografts showed T-cell infiltration in perivascular areas from day 1, but tubulitis and arteritis did not develop until day 7. Flow cytometry confirmed the early allospecific CD3 + CD8 + T-cell infiltrate. At day 1, both allografts and isografts showed extensive transcriptome changes, reflecting the response to surgery, but only allografts show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 42 publications
(12 reference statements)
1
30
0
Order By: Relevance
“…Acute allograft rejection is a T-or B-cell-mediated process associated with a stereotyped, inflammatory response involving cells of the adaptive and innate immune systems (23)(24)(25). Experiments in animal models showed that although acute rejection is initiated by T cells, the damage to the allograft parenchyma appears concurrent with monocyte recruitment and massive inflammation (26). Because monocytes are known to secrete inflammatory cytokines, notably IL-1b, IL-6, and TNF-a, in renal transplant recipients (8), it follows that the inflammatory process occurring during an acute rejection episode would translate into measurable changes in the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…Acute allograft rejection is a T-or B-cell-mediated process associated with a stereotyped, inflammatory response involving cells of the adaptive and innate immune systems (23)(24)(25). Experiments in animal models showed that although acute rejection is initiated by T cells, the damage to the allograft parenchyma appears concurrent with monocyte recruitment and massive inflammation (26). Because monocytes are known to secrete inflammatory cytokines, notably IL-1b, IL-6, and TNF-a, in renal transplant recipients (8), it follows that the inflammatory process occurring during an acute rejection episode would translate into measurable changes in the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…They serve as an annotation tool, with which genes identified in our analysis can be assigned to biological processes relevant to transplantation. PBTs were derived previously from mouse transplant models and in vitro human cell lines (15,29,30,(34)(35)(36)(37)(38)(39)(40). The definitions and algorithms for the PBTs referenced in the tables can be found in Supplemental Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…IL1B, TNF, and OSM are the part of the inflammasome in macrophages and contribute to the response to wounding (53,62). It may be significant that OSMR, ITGB6, and MIR21 are among the top TxBx-corrected transcripts.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%